Positive electrode sheet and battery

CN122677385APending Publication Date: 2026-09-01JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611000809.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

但是金属锂等补锂材料的化学活性很高,易与正极浆料中的溶剂或空气中的水、氧气发生反应,导致浆料稳定性变差;同时,补锂材料与正极活性材料(例如磷酸铁锂等)颗粒间界面相容性差,循环过程中易出现界面阻抗升高等问题,影响电池长期循环性能

Benefits of technology

[0027]本申请实施例中,补锂剂的内核作为核心补锂源,可以提供活性锂离子,第一包覆层作为导离子不导电子层,可以阻断内核与第二包覆层的电子通路,避免内部出现短路,以及形成致密的防护界面,阻断内核与空气、电解液的直接接触,从而减少内核的腐蚀、氧化及产气等不可逆损耗,而且第一包覆层通过自身结构特性(致密度大于等于92%)可以构建锂离子传输的速率调控屏障,控制内核的释锂速率,避免释锂速率过快而导致的锂析出与副反应,以及防止内核因快速释锂可能引发的过度体积膨胀,从而保障内核稳定、可控地释放锂离子;第二包覆层包括与正极活性材料相同的界面修饰材料,可以消除异质界面的晶格失配与电荷积累,大幅降低补锂剂与正极活性材料的界面阻抗,提升离子和/或电子传输效率,而且第二包覆层自身结构特性(致密度小于等于80%),使得第二包覆层具有相对疏松的结构,存在大量孔隙与连通通道,可以促进电解液浸润,为锂离子提供快速迁移的通道,降低界面阻抗;同时,相对疏松的第二包覆层具备弹性缓冲空间,可通过自身孔隙的压缩与回弹,降低内核膨胀带来的包覆层破裂的风险。此外,相对疏松的第二包覆层的表面粗糙度更高,能与正极活性材料或隔膜形成更稳定的物理接触,减少界面滑移,提升界面兼容性,进一步降低界面阻抗。由上可知,本申请实施例中,第一包覆层和第二包覆层共同形成双重物理隔绝体系,可大幅提升对内核的防护效果,显著抑制补锂剂产气抑和提升电池循环性能,内核释放的锂离子通过第一包覆层的“限速传输”和第二包覆层的“快速传输”形成梯度传输路径,既可以避免内核瞬时大量释锂引发的安全问题,又能保证锂离子快速输送至正极,为正极补充首次充放电过程中因SEI膜的形成、活性材料不可逆相变等产生的不可逆锂损失,从而提升电池的首次库伦效率。即本申请实施例中,通过第一包覆层和第二包覆层的协同作用,不仅可以保障补锂剂内核的稳定,还能保障锂离子的可控释放和快速传输和优化界面接触,提升补锂剂锂源利用率,匹配电极整体的电化学特性,降低界面阻抗,从而可以保障电池的安全性能以及提升电池的首次库伦效率和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122677385A_ABST
    Figure CN122677385A_ABST
Patent Text Reader

Abstract

The application relates to a positive electrode sheet and a battery, the positive electrode sheet comprising a current collector and an active material layer arranged on at least one side surface of the current collector in the thickness direction; the active material layer comprising a positive electrode active material and a lithium supplement agent; the lithium supplement agent being in a core-shell structure, comprising an inner core and a first coating layer and a second coating layer successively coating the inner core from inside to outside; the inner core comprising metallic lithium and / or a lithium alloy, the material of the first coating layer being an ion-conducting and electron-non-conducting material, the second coating layer comprising an interface modification material, the interface modification material being the same as the positive electrode active material; the compactness of the first coating layer being greater than or equal to 92%, and the compactness of the second coating layer being less than or equal to 80%. In this way, through the synergistic effect of the first coating layer and the second coating layer, the stability of the inner core of the lithium supplement agent can be ensured, the controllable release and rapid transmission of lithium ions can be ensured, and the interface contact can be optimized, so that the safety performance of the battery can be ensured, and the first coulomb efficiency and the cycle performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a positive electrode and a battery. Background Technology

[0002] Lithium iron phosphate (LFP) batteries have been widely used in new energy vehicles and energy storage due to their advantages such as high safety, low cost, and long cycle life. However, the LFP cathode suffers irreversible lithium loss during the first charge and discharge process. This loss mainly stems from the formation of the solid electrolyte interphase (SEI) film on the anode surface and the irreversible extraction of lattice lithium, resulting in a low initial coulombic efficiency.

[0003] Existing technologies typically add lithium replenishment materials (such as lithium metal powder) to the positive electrode to compensate for irreversible lithium loss during the first charge-discharge process. However, lithium replenishment materials such as lithium metal are highly chemically reactive and easily react with solvents in the positive electrode slurry or with water and oxygen in the air, leading to poor slurry stability. At the same time, the interfacial compatibility between the lithium replenishment materials and the positive electrode active materials (such as lithium iron phosphate) is poor, and problems such as increased interfacial impedance can easily occur during cycling, affecting the long-term cycle performance of the battery. Summary of the Invention

[0004] In view of this, embodiments of this application provide a positive electrode and a battery to solve at least one problem existing in the prior art.

[0005] In a first aspect, embodiments of this application provide a positive electrode sheet, including a current collector and an active material layer disposed on at least one side surface of the current collector along the thickness direction; the active material layer includes a positive electrode active material and a lithium supplementing agent;

[0006] The lithium replenishing agent has a core-shell structure, including a core and a first coating layer and a second coating layer that sequentially cover the core from the inside out; the core includes metallic lithium and / or lithium alloy, the material of the first coating layer is an ion-conducting but non-conducting electronic material, the second coating layer includes an interface modification material, the interface modification material being the same as the positive electrode active material; the density of the first coating layer is greater than or equal to 92%, and the density of the second coating layer is less than or equal to 80%.

[0007] In conjunction with the first aspect of this application, in an optional embodiment, the particle size of the kernel is 1 μm to 5 μm.

[0008] In conjunction with the first aspect of this application, in an alternative embodiment,

[0009] The material of the first coating layer includes at least one of Li3PO4, LiAlO2, Al2O3, ZrO2, and Li3N, preferably Li3PO4; and / or,

[0010] The interface modification material includes at least one of lithium iron phosphate, lithium vanadium phosphate, ternary cathode material, lithium manganese oxide, and lithium cobalt oxide, preferably lithium iron phosphate.

[0011] In conjunction with the first aspect of this application, in an optional embodiment, the second coating layer further includes a conductive agent; optionally, the mass ratio of the interface modification material to the conductive agent is (85~95):(5~15).

[0012] In conjunction with the first aspect of this application, in an optional embodiment, the mass ratio of the first coating layer to the second coating layer is (20~40):(60~80).

[0013] In conjunction with the first aspect of this application, in an alternative embodiment,

[0014] The thickness of the first coating layer is 80nm~250nm; and / or,

[0015] The thickness of the second coating layer is 100nm~320nm.

[0016] In conjunction with a first aspect of this application, in an optional embodiment, the second coating layer includes a first sublayer and a second sublayer, the first sublayer being located between the first coating layer and the second sublayer, and the density of the first sublayer being greater than the density of the second sublayer.

[0017] In conjunction with the first aspect of this application, in an alternative embodiment,

[0018] The compactness of the first sublayer is greater than or equal to 40%; and / or,

[0019] The density of the second sublayer is 25%~35%; and / or,

[0020] The thickness of the first sublayer is 100nm~300nm; and / or,

[0021] The thickness of the second sublayer is 5nm~20nm, preferably 10nm~15nm.

[0022] In conjunction with the first aspect of this application, in an alternative embodiment,

[0023] The mass ratio of the lithium supplement to the positive electrode active material is (1~5):100; and / or,

[0024] The particle size ratio of the lithium supplement to the positive electrode active material is 1:(5~10).

[0025] Secondly, embodiments of this application provide a battery including the positive electrode sheet described in any of the first aspects.

[0026] Compared with the prior art, the embodiments of this application have the following beneficial effects:

[0027] In this embodiment, the core of the lithium replenishing agent serves as the core lithium source, providing active lithium ions. The first coating layer, acting as an ion-conducting but non-conducting electron layer, blocks the electronic pathway between the core and the second coating layer, preventing internal short circuits and forming a dense protective interface. This blocks direct contact between the core and air or electrolyte, reducing irreversible losses such as corrosion, oxidation, and gas generation. Furthermore, the first coating layer, through its structural characteristics (density greater than or equal to 92%), can construct a rate-regulating barrier for lithium ion transport, controlling the lithium release rate of the core and preventing lithium deposition and side reactions caused by excessively rapid lithium release. It also prevents excessive volume expansion of the core that may be caused by rapid lithium release, thus protecting the core. The second coating layer provides stable and controllable lithium-ion release. It includes the same interface modification material as the positive electrode active material, which eliminates lattice mismatch and charge accumulation at the heterogeneous interface, significantly reducing the interfacial impedance between the lithium supplement and the positive electrode active material, and improving ion and / or electron transport efficiency. Furthermore, the structural characteristics of the second coating layer (density ≤ 80%) result in a relatively loose structure with numerous pores and interconnected channels, promoting electrolyte wetting and providing a rapid migration path for lithium ions, thus reducing interfacial impedance. Simultaneously, the relatively loose second coating layer provides elastic buffer space, reducing the risk of coating layer breakage due to core expansion through compression and rebound of its own pores. In addition, the relatively loose second coating layer has a higher surface roughness, enabling more stable physical contact with the positive electrode active material or separator, reducing interfacial slippage, improving interfacial compatibility, and further reducing interfacial impedance. As can be seen from the above, in this embodiment, the first and second coating layers together form a dual physical isolation system, which can significantly improve the protection effect on the core, significantly suppress the gas generation of the lithium replenishing agent and improve the battery cycle performance. The lithium ions released from the core form a gradient transport path through the "rate-limiting transport" of the first coating layer and the "rapid transport" of the second coating layer. This can avoid the safety problems caused by the instantaneous release of a large amount of lithium from the core, and ensure that lithium ions are quickly transported to the positive electrode to replenish the irreversible lithium loss caused by the formation of the SEI film and the irreversible phase transition of the active material during the first charge and discharge process, thereby improving the battery's first coulombic efficiency. That is, in this embodiment, through the synergistic effect of the first and second coating layers, not only can the stability of the lithium replenishing agent core be ensured, but also the controllable release and rapid transport of lithium ions and the optimization of interface contact can be ensured, improving the lithium source utilization rate of the lithium replenishing agent, matching the overall electrochemical characteristics of the electrode, and reducing interface impedance, thereby ensuring the battery's safety performance and improving the battery's first coulombic efficiency and cycle performance.

[0028] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0029] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:

[0030] Figure 1 This is a schematic diagram of the structure of a lithium replenishing agent provided in an embodiment of this application. Detailed Implementation

[0031] To make the technical solution and beneficial effects of the present invention more apparent and understandable, a detailed description is provided below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional experimental conditions. Unless otherwise specified, all reagents and raw materials used in this invention are commercially available.

[0032] In the following description, numerous specific details are set forth in order to provide a more thorough understanding of this application. However, it will be apparent to those skilled in the art that this application can be practiced without one or more of these details. In other instances, to avoid confusion with this application, some technical features well-known in the art have not been described; that is, not all features of actual embodiments are described herein, nor are well-known functions and steps described in detail.

[0033] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. When used herein, the singular forms “a,” “an,” and “the” are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the terms “comprising” and / or “including,” when used in this specification, identify the presence of the stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups. When used herein, the term “and / or” includes any and all combinations of the associated listed items.

[0034] To fully understand this application, detailed steps and structures will be presented in the following description to illustrate the technical solution of this application. Preferred embodiments of this application are described in detail below; however, in addition to these detailed descriptions, this application may have other implementation methods.

[0035] Unless otherwise defined, the technical and scientific terms used in this application have the same meanings as those in the technical and scientific field to which this application pertains.

[0036] Unless otherwise specified, the techniques or conditions described in the following embodiments are generally performed in accordance with conventional techniques or conditions described in the literature in this field, or in accordance with the product manual and the manufacturer's recommendations. All numerical ranges in the following embodiments include endpoint values.

[0037] In related technologies, a single coating layer (such as a carbon coating layer or an oxide coating layer) is used to coat the lithium replenishment material to improve its stability. While this approach can improve the stability of the lithium replenishment material to some extent, it cannot simultaneously achieve both "controllable release during the lithium replenishment process" and "interface matching with the positive electrode active material." Specifically, although a single carbon coating layer has good conductivity, its lithium-ion transport efficiency is low, causing a mismatch between the lithium replenishment rate and the positive electrode delithiation rate; while a single oxide coating layer can isolate side reactions, its own conductivity is poor, easily leading to an increase in the overall impedance of the electrode. In other words, it is difficult to simultaneously achieve stability of the lithium replenishment material, lithium replenishment effect, and interface improvement.

[0038] Based on this, embodiments of this application provide a positive electrode sheet, which includes a current collector and an active material layer disposed on at least one side surface of the current collector along its thickness direction; the active material layer includes a positive electrode active material and a lithium supplementing agent; such as Figure 1 As shown, the lithium replenisher has a core-shell structure, including a core 100 and a first coating layer 110 and a second coating layer 120 that sequentially coat the core 100 from the inside out; the core 100 includes metallic lithium and / or lithium alloy, the material of the first coating layer 110 is an ion-conducting but non-electronic material, and the second coating layer 120 includes an interface modification material, which is the same as the positive electrode active material; the density of the first coating layer 110 is greater than or equal to 92%, and the density of the second coating layer 120 is less than or equal to 80%.

[0039] In this embodiment, the core 100 of the lithium replenishing agent serves as the core lithium source, providing active lithium ions. The first coating layer 110, as an ion-conducting but non-conducting electron layer, blocks the electronic pathway between the core 100 and the second coating layer 120, preventing internal short circuits and forming a dense protective interface to block direct contact between the core 100 and air and electrolyte, thereby reducing irreversible losses such as corrosion, oxidation, and gas generation of the core 100. Furthermore, the first coating layer 110, through its structural characteristics (density greater than or equal to 92%), can construct a rate-regulating barrier for lithium ion transport, controlling the lithium release rate of the core 100, preventing lithium deposition and side reactions caused by excessively rapid lithium release, and preventing excessive volume expansion of the core 100 due to rapid lithium release, thus ensuring stable and controllable lithium ion release from the core 100; the second coating layer 120... The second coating layer 120 includes the same interface modification material as the positive electrode active material, which can eliminate lattice mismatch and charge accumulation at the heterogeneous interface, significantly reduce the interfacial impedance between the lithium supplement and the positive electrode active material, and improve ion and / or electron transport efficiency. Furthermore, the structural characteristics of the second coating layer 120 (density less than or equal to 80%) result in a relatively loose structure with numerous pores and interconnected channels, promoting electrolyte wetting and providing a rapid migration channel for lithium ions, thus reducing interfacial impedance. Simultaneously, the core 100, including metallic lithium and / or lithium alloys, undergoes significant volume deformation during deposition / stripping, with a volume expansion rate exceeding 300%. The relatively loose second coating layer 120 provides an elastic buffer space, reducing the risk of coating layer rupture caused by core 100 expansion through compression and rebound of its own pores. In addition, the relatively loose second coating layer 120 has a higher surface roughness, enabling more stable physical contact with the positive electrode active material or separator, reducing interfacial slippage, improving interfacial compatibility, and further reducing interfacial impedance. As can be seen from the above, in this embodiment of the application, the first coating layer 110 and the second coating layer 120 together form a dual physical isolation system, which can significantly improve the protection effect on the core 100, significantly suppress the generation of lithium replenishing agent and improve the battery cycle performance. The lithium ions released by the core 100 form a gradient transport path through the "speed-limiting transport" of the first coating layer 110 and the "rapid transport" of the second coating layer 120. This can not only avoid the safety problem caused by the instantaneous large-scale lithium release of the core 100, but also ensure that lithium ions are quickly transported to the positive electrode, replenishing the irreversible lithium loss caused by the formation of the SEI (solid electrolyte interface) film and the irreversible phase transition of the active material during the first charge and discharge process, thereby improving the battery's first coulombic efficiency.In the embodiments of this application, the synergistic effect of the first coating layer 110 and the second coating layer 120 can not only ensure the stability of the lithium replenishment core 100, but also ensure the controllable release and rapid transport of lithium ions and optimize interface contact, improve the lithium source utilization rate of the lithium replenishment, match the overall electrochemical characteristics of the electrode, and reduce interface impedance, thereby ensuring the safety performance of the battery and improving the initial coulombic efficiency and cycle performance of the battery.

[0040] In this embodiment, the active material layer can be disposed on one side surface of the current collector along the thickness direction, or on both sides surface of the current collector along the thickness direction. The positive electrode active material in the active material layer can be, for example, at least one of lithium iron phosphate (LFP), lithium vanadium phosphate (Li3V2(PO4)3), ternary cathode materials (also known in the industry as ternary layered oxides), lithium manganese oxide (LiMn2O4), and lithium cobalt oxide (LCO). In a specific example, the positive electrode active material can be, for example, lithium iron phosphate.

[0041] For example, the core 100 can be metallic lithium and / or a lithium alloy (specifically, for example, a Li-Al alloy, a Li-Si alloy, a Li-Mg alloy, etc.). During the initial charging of the battery, the core 100 undergoes an oxidation reaction to generate lithium ions, thereby playing a role in lithium replenishment.

[0042] It is understandable that when the particle size of the core 100 is too large, it will lead to a longer lithium-ion transport path, making it difficult for lithium atoms inside the core 100 to be completely oxidized and release lithium ions, thus affecting the utilization rate of the core 100. Moreover, the large particle size of the core 100 results in a high volume expansion rate during charging and discharging, which may break through the dense first coating layer 110, causing problems such as lithium dendrite growth and side reactions and gas generation when the core 100 comes into contact with the electrolyte. In addition, the excessively large particle size of the core 100 will also increase the difficulty of the coating process, for example, the first coating layer 110 is not easy to uniformly cover the core 100. The surface of the core 100 is prone to localized exposed defects. When the particle size of the core 100 is too small, its specific surface area becomes too large. In the actual preparation process of the lithium replenishment agent, the core 100 is prone to agglomeration when in contact with the material of the first coating layer 110, resulting in uneven coating thickness and weakening its effect on controlling the lithium release rate. In addition, the small-diameter core 100 particles have high surface energy and are easily oxidized by air during storage and preparation, prematurely consuming the lithium source, reducing the lithium replenishment efficiency, and increasing the cost of industrial production. Moreover, the preparation and dispersion process of ultrafine lithium powder is complex, and batch stability is difficult to control. Therefore, in some embodiments, the particle size of the core 100 can be 1μm~5μm, for example, 1μm, 2μm, 3μm, 4μm, 5μm or any value between any two of the above ranges. This can balance the stability, lithium replenishment performance and production cost of the lithium replenishment agent.

[0043] In this embodiment, the core 100 serves as a lithium replenishment source and does not require electron transport. That is, the core 100 only serves as a lithium replenishment source and does not participate in electron conduction. Therefore, the material of the first coating layer 110 can be an ion-conducting but non-electron-conducting material. This can block the electronic pathway between the core 100 and the second coating layer 120, avoid internal short circuits, and ensure the transport of lithium ions released by the core 100.

[0044] In some embodiments, the material of the first coating layer 110 may include at least one of Li3PO4, LiAlO2, Al2O3, ZrO2, and Li3N. Specifically, the material of the first coating layer 110 may be at least one of Li3PO4, LiAlO2, Al2O3, ZrO2, and Li3N.

[0045] In some specific embodiments, the material of the first coating layer 110 is preferably Li3PO4.

[0046] Using Li3PO4 as the material for the first coating layer 110 has the following four advantages: First, Li3PO4 has a fast lithium-ion transport channel, which can ensure the controlled-rate lithium release of the core 100. At the same time, it is an electronic insulator, which can isolate electronic pathways and inhibit the nucleation and growth of lithium dendrites from the root. Second, Li3PO4 has excellent chemical and electrochemical stability, and does not undergo side reactions with lithium metal or electrolyte. This can effectively avoid corrosion and gas generation problems caused by direct contact between the core 100 and the electrolyte, and ensures good structural integrity of the first coating layer 110 under long-term cycling. Third, Li3PO4... O4 has good mechanical strength and thermal stability. Li3PO4 itself has high rigidity and can withstand more than 100% volume expansion during the charging and discharging of the core 100, preventing the first coating layer 110 from cracking. Moreover, Li3PO4 has a high melting point and decomposition temperature, and its structure is not easy to collapse under high temperature conditions, thus improving the safety threshold of the cell. Fourth, Li3PO4 has good process adaptability. In the actual preparation process of lithium replenishment, a uniform and dense first coating layer 110 can be prepared by various methods such as sol-gel method and atomic layer deposition (ALD), which is easy to realize industrial mass production, and the thickness of the first coating layer 110 is highly controllable.

[0047] The first coating layer 110 is a dense Li3PO4 layer. The speed-controlled transport of lithium ions can be achieved through the lattice gaps / vacancies of the Li3PO4 layer. This can prevent a large number of lithium ions from entering the electrolyte instantly, causing lithium dendrite precipitation and violent gas production. It can also block the electronic short circuit between the core lithium source (core 100) and the positive electrode by virtue of its insulating properties.

[0048] It should be noted that in this application, the first coating layer 110 can completely cover the surface of the core 100. Here, "complete coverage" can be understood as the first coating layer 110 completely covering the surface of the core 100 within the allowable tolerances of the coating process. Similarly, within the allowable tolerances of the coating process, the second coating layer 120 completely covers the surface of the first coating layer 110.

[0049] The interface modification material in the second coating layer 120 is the same as the positive electrode active material. The interface modification material may include, for example, at least one of lithium iron phosphate, lithium vanadium phosphate, ternary cathode materials, lithium manganese oxide, and lithium cobalt oxide. Specifically, the interface modification material may be at least one of lithium iron phosphate, lithium vanadium phosphate, ternary cathode materials, lithium manganese oxide, and lithium cobalt oxide.

[0050] In some specific embodiments, the interface modification material is preferably lithium iron phosphate. It is understood that in this case, the positive electrode active material is also lithium iron phosphate.

[0051] Using lithium iron phosphate as the interface modification material has the following four advantages: First, lithium iron phosphate has a high lattice matching degree with the material of the first coating layer 110 (especially Li3PO4), which can reduce the interface impedance; second, lithium iron phosphate has small volume strain during charging and discharging, and its structure is more stable, which can alleviate the overall expansion of the positive electrode sheet; third, lithium iron phosphate has strong chemical inertness and good compatibility with electrolyte, which is conducive to improving the overall performance of the battery; fourth, the preparation process of lithium iron phosphate is mature, easy to be compatible with existing production lines, and has low industrialization cost.

[0052] In some embodiments, please refer to Figure 1 The second coating layer 120 may also include a conductive agent 121. The conductive agent 121 can form a continuous conductive network in the second coating layer 120, that is, construct a continuous electron transport network, reduce the electronic impedance of the second coating layer 120, and enhance the structural connectivity of the second coating layer 120, ensuring the efficient transport of ions and electrons, thereby ensuring the continuous and efficient electrochemical reaction and meeting the requirements of high-rate charge and discharge.

[0053] For example, the conductive agent 121 may be at least one of acetylene black, conductive carbon black (SP), graphene, carbon nanotubes, and Ketjen black.

[0054] In addition, the electrolyte typically includes additives such as fluoroethylene carbonate (FEC) and vinylene carbonate (VC). These additives can be directionally reduced on the surface of the carbon-based conductive network formed by the conductive agent 121 in the second coating layer 120, forming a dense, low-resistance, and non-breakable interfacial protective film, thereby effectively inhibiting the continuous decomposition of the electrolyte and improving the cycle performance of the battery.

[0055] It is understandable that when the mass ratio of interface modification material to conductive agent 121 is too large, it is not conducive to the formation of a continuous electron transport network in the second coating layer 120. The electronic impedance of the second coating layer 120 increases, the lithium-ion insertion / extraction reaction is hindered, and the utilization rate of the lithium replenisher decreases, thereby affecting the rate performance and cycle life of the battery. When the mass ratio of interface modification material to conductive agent 121 is too small, the proportion of the same interface modification material as the positive electrode active material is too small, the ion transport channels are reduced, and the interface impedance between the lithium replenisher and the positive electrode active material increases. Moreover, a large amount of conductive agent 121 will also increase the contact area with the electrolyte, triggering additional side reactions, increasing gas production, thereby reducing the battery's safety performance, cycle performance, and energy density. Therefore, in some specific embodiments, the mass ratio of the interface modification material to the conductive agent 121 can be (85~95):(5~15), for example, 85:5, 85:10, 85:15, 90:5, 90:10, 90:15, 95:5, 95:10, 95:15, or any value between any two of the above ranges. This allows for a balance between the battery's rate performance, cycle life, safety performance, and energy density.

[0056] In this embodiment, if the mass ratio of the first coating layer 110 to the second coating layer 120 is too small, the mass proportion of the first coating layer 110 will be too small, making it difficult to form a continuous and dense protection and lithium compensation channel on the surface of the core 100. This will reduce the controlled-rate lithium release capability of the core 100. Furthermore, during charge-discharge cycles, due to the limited protective effect of the first coating layer 110, the core 100 is prone to contact with the electrolyte, triggering side reactions and affecting the cycle stability and safety performance of the battery. Simultaneously, the relatively loose second coating layer 120 lacks sufficient support and may pulverize or detach during the volume expansion and contraction of the lithium replenishment agent, thereby reducing... The integrity of the lithium replenishment structure; when the mass ratio of the first coating layer 110 and the second coating layer 120 is too large, the mass proportion of the second coating layer 120 will be too small. Since the interface modification material in the second coating layer 120 is the same as the positive electrode active material, it can provide the capacity, thus leading to a decrease in the energy density of the battery. Moreover, an excessively thick second coating layer 120 will prolong the lithium ion transport path and increase the interface impedance, thereby affecting the rate performance of the battery. In addition, when the mass proportion of the second coating layer 120 material is too high, it is also easy to induce agglomeration, destroy the uniformity of the electrode, cause excessive local current density, and have the risk of inducing lithium dendrite growth. Therefore, in some embodiments, the mass ratio of the first coating layer 110 to the second coating layer 120 can be (20~40):(60~80), for example, it can be 20:60, 20:70, 20:80, 30:60, 30:70, 30:80, 40:60, 40:70, 40:80, or any value between any two of the above ranges. This allows the first coating layer 110 and the second coating layer 120 to better work synergistically, thereby achieving a better balance between the battery's rate performance, cycle life, safety performance, and energy density.

[0057] When the first coating layer 110 is too thick, the material of the first coating layer 110 is prone to agglomeration during the coating process, resulting in uneven thickness of the first coating layer 110, which affects its controlled lithium release effect. When the first coating layer 110 is too thin, it is not easy to form a continuous and dense protective barrier on the surface of the core 100. The electrolyte is easy to penetrate to the surface of the core 100, causing side reactions to produce gas and lithium dendrites to grow, which affects the battery safety performance and cycle stability. Moreover, an excessively thin first coating layer 110 is not easy to achieve precise controlled lithium release. The lithium metal and / or lithium alloy in the core 100 are easy to be quickly oxidized and depleted, leading to uncontrolled lithium replenishment. In addition, the thickness uniformity of an excessively thin first coating layer 110 is also difficult to guarantee, and local "pinhole" defects are prone to occur, becoming potential points for electronic short circuits. Therefore, in some embodiments, the thickness of the first coating layer 110 can be 80nm to 250nm, for example, it can be 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 250nm or any value between any two of the above ranges.

[0058] When the second coating layer 120 is too thick, the ion and electron transport paths are prolonged, leading to increased impedance and slower electrochemical reaction kinetics between the lithium replenishment particles and the positive electrode active material, resulting in a decrease in battery rate performance. Furthermore, an excessively thick second coating layer 120 also compresses the loading space of the positive electrode active material, reducing the overall energy density of the battery. Additionally, an excessively thick second coating layer 120 may easily lead to interlayer delamination, potentially preventing it from continuously providing protection during cycling and causing faster battery capacity decay. When the second coating layer 120 is too thin... The formation of a continuous conductive network and ion channels can worsen the interface matching between the lithium replenisher and the positive electrode active material, increasing interface impedance and reducing the utilization rate of the lithium replenisher. Furthermore, the secondary protective barrier constructed by the second coating layer 120 has limited protective effect, allowing electrolyte penetration and increasing the probability of contact between the core 100 and the electrolyte. In addition, the thickness uniformity of an excessively thin second coating layer 120 is difficult to guarantee, leading to localized coating gaps and reduced synergy with the first coating layer 110, thus affecting the battery's safety performance and cycle stability. Therefore, in some embodiments, the thickness of the second coating layer 120 can be 100nm~320nm, for example, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, or any value between any two of the above ranges.

[0059] In some embodiments, the second coating layer 120 may include a first sublayer (not shown) and a second sublayer (not shown), with the first sublayer located between the first coating layer 110 and the second sublayer, and the density of the first sublayer being greater than that of the second sublayer. This creates a density gradient in the second coating layer 120 that decreases along a direction away from the first coating layer 110, thereby further promoting lithium-ion transport in the second coating layer 120 and thus improving lithium replenishment efficiency and interface resistance.

[0060] In some embodiments, the compactness of the first sublayer can be greater than or equal to 40% and less than or equal to 80%. Specifically, it can be 40%, 50%, 60%, 70%, 80%, or any value between any two of the above ranges.

[0061] In some embodiments, the density of the second sublayer can be 25% to 35%, for example, it can be 25%, 30%, 35% or any value between any two of the above ranges.

[0062] Controlling the density of at least one of the first and second sublayers within the aforementioned range helps ensure the wetting of the second coating layer 120 by the electrolyte, promotes lithium-ion transport, maintains the integrity of the electron conduction network in the second coating layer 120, and also helps ensure the suppression of volume expansion of the core 100 by the second coating layer 120, ensuring the stability of the lithium replenishment structure. This reduces the battery's internal resistance and improves the battery's initial coulombic efficiency and cycle performance.

[0063] In some embodiments, the thickness of the first sublayer can be 100nm to 300nm, for example, it can be 100nm, 150nm, 200nm, 250nm, 300nm or any value between any two of the above ranges.

[0064] In some embodiments, the thickness of the second sublayer can be 5nm to 20nm, for example, it can be 5nm, 10nm, 15nm, 20nm or any value between any two of the above ranges, preferably 10nm to 15nm.

[0065] Controlling the thickness of at least one of the first and second sublayers within the aforementioned range is beneficial for balancing the protective effect and ion transport efficiency of the second coating layer 120.

[0066] In some embodiments, the mass ratio of lithium supplement to positive electrode active material can be (1~5):100, for example, it can be 1:100, 2:100, 3:100, 4:100, 5:100 or any value between any two of the above ranges.

[0067] When the mass ratio of lithium replenisher in the active material layer is too high, it will compress the loading space of the positive electrode active material, leading to a decrease in battery energy density. Furthermore, a large amount of lithium replenisher can easily trigger side reactions in the electrolyte, resulting in increased gas production and affecting cycle stability. In addition, the first electronically insulating coating layer 110 in the lithium replenisher will increase the overall battery impedance, affecting rate performance. When the mass ratio of lithium replenisher in the active material layer is too low, the lithium replenishment dosage may not be sufficient to fully compensate for irreversible lithium losses caused by SEI film formation and phase transitions in the positive electrode active material, resulting in limited improvement in the battery's initial coulombic efficiency. Therefore, controlling the mass ratio of lithium replenisher to positive electrode active material to (1~5):100 can effectively improve the initial coulombic efficiency while also considering the battery's energy density and cycle stability.

[0068] In some embodiments, the particle size ratio of the lithium supplement to the positive electrode active material can be 1:(5~10), for example, it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any value between any two of the above ranges.

[0069] When the particle size ratio of the lithium replenisher to the positive electrode active material is too large, the lithium replenisher particle size approaches or exceeds that of the positive electrode active material, making it difficult for the lithium replenisher particles to disperse uniformly within the gaps between the positive electrode active material particles. This leads to localized agglomeration, and during charge and discharge, localized volume expansion causes stress concentration, which can easily damage the positive electrode structure and affect cycle life. Conversely, when the particle size ratio is too small, the lithium replenisher particles are too small, resulting in a large specific surface area and high surface energy. During the positive electrode preparation process, this can easily lead to agglomeration during the preparation of the positive electrode slurry, weakening the lithium replenishment effect. Furthermore, excessively small lithium replenisher particles may block the ion transport channels of the positive electrode active material, increasing interfacial impedance. Therefore, controlling the particle size ratio of the lithium replenisher to the positive electrode active material to 1:(5~10) ensures uniform dispersion of the lithium replenisher, thereby guaranteeing the lithium replenishment effect. Simultaneously, it also ensures the stability of the positive electrode, reduces interfacial impedance, and improves the cycle life of the battery.

[0070] The method for preparing the positive electrode in any of the above embodiments may include the following steps:

[0071] S1: A first coating layer and a second coating layer are sequentially coated from the inside out on the surface of metallic lithium and / or lithium alloy (core) to obtain a lithium replenishing agent; wherein, the material of the first coating layer is an ion-conducting but non-electronic material, and the second coating layer includes an interface modification material, which is the same as the positive electrode active material used in the positive electrode sheet; the density of the first coating layer is greater than or equal to 92%, and the density of the second coating layer is less than or equal to 80%;

[0072] S2: Add the positive electrode active material, the lithium supplement agent, the positive electrode conductive agent and the binder obtained in step S1 to a solvent (specifically, N-methylpyrrolidone, deionized water, etc.), and vacuum stir at a speed of 2000 rpm to 3000 rpm for 2 h to 4 h to prepare a positive electrode slurry with a solid content of 50% to 60%.

[0073] S3: The positive electrode slurry obtained in step S2 is coated on at least one side surface of the positive electrode current collector (specifically, aluminum foil) along the thickness direction to form a wet film with a thickness of 100μm~200μm; after drying in a forced air at 80℃~120℃ for 2h~4h, it is rolled under a pressure of 5MPa~10MPa to obtain a dry film (i.e., active material layer) with a thickness of 50μm~100μm, thus obtaining the positive electrode sheet.

[0074] In step S1, taking the first coating layer as Li3PO4, the interface modification material as LiFePO4, and the second coating layer as including a first sublayer and a second sublayer (the first sublayer is located between the first coating layer and the second sublayer, and the density of the first sublayer is greater than that of the second sublayer) as an example, the steps for preparing the lithium supplement can include: First, dispersing metallic lithium and / or lithium alloy particles in an alcohol solution containing phosphate ions, and reacting at 30℃~50℃ for 1h~2h under inert gas protection to form a Li3PO4 inner layer (i.e., the first coating layer); Next, adding LiFePO4 powder and a conductive agent, ultrasonically dispersing, stirring at 80℃~100℃ for 3h~5h, and then calcining at 400℃~500℃ under an inert atmosphere for 2h. After 3 hours, the first sublayer is coated onto the inner surface of Li3PO4 to obtain a core-shell intermediate. Next, LiFePO4 powder, binder (e.g., PVDF), and solvent (e.g., NMP) are mixed and stirred to form an outermost slurry with a solid content of 50%~60%. The viscosity is adjusted to 2000mPa·s~3000mPa·s. The core-shell intermediate is added to the outermost slurry and ultrasonically dispersed for 30min~60min to ensure uniform coating on the surface of the core-shell intermediate. Then, a fluidized bed coating process is used for coating, with the fluidization velocity controlled at 0.8m / s~1.2m / s and the coating temperature at 60℃~80℃, until the density of the second sublayer reaches 25%~35%. After sieving, the lithium supplement is obtained.

[0075] In step S1 above, the density and thickness of the first coating layer, the first sublayer, and the second sublayer can be adjusted by controlling the amount of raw materials fed and the process conditions. Specifically, the theoretical amount of coating material to be fed can be calculated by measuring the specific surface area of ​​the core and the target thickness and density of the coating layer. Process parameters such as reaction temperature and time, calcination temperature and time, and fluidized bed coating wind speed and temperature are then adjusted sequentially. Through iterative optimization using multiple sets of comparative experiments, the correspondence between the target thickness and density of the coating layer and the amount of raw materials fed and the process conditions is determined. In the above process, the thickness of each coating layer of the prepared material is obtained by cross-sectional observation using FIB (Focused Ion Beam)-TEM (Transmission Electron Microscopy). Twenty particles are randomly selected, and multiple points of the coating layer to be tested are measured, with the average value taken to obtain the coating layer thickness.

[0076] This application also provides a battery comprising the positive electrode sheet described in any of the foregoing embodiments.

[0077] It is understood that the beneficial effects of the positive electrode sheet in any of the foregoing embodiments are also applicable to the battery in the embodiments of this application.

[0078] The technical solution of this application will be further described below with reference to several embodiments and comparative examples.

[0079] Example 1

[0080] The method for preparing the positive electrode sheet in this embodiment includes the following steps:

[0081] Step S101: First, Li-Mg alloy particles with a particle size of 2 μm (Li mass fraction 70%) are dispersed in a 0.3 mol / L dimethyl phosphate ethanol solution. Under argon protection, the mixture is reacted at 40°C for 1.5 h to form a Li3PO4 inner layer (first coating layer) with a thickness of 170 nm and a density of 95% on the surface of the Li-Mg alloy particles. Then, lithium iron phosphate powder (interface modification material) and SP (conductive agent) are added to the above solution system (mass ratio of lithium iron phosphate powder to Li3PO4 is 7:3, and mass ratio of lithium iron phosphate powder to SP is 9:1). After ultrasonic dispersion, the mixture is stirred at 90°C for 4 h and then calcined at 450°C for 2 h under an argon atmosphere. After 5 hours, a first sublayer with a thickness of 200 nm and a density of 60% is formed, resulting in a core-shell intermediate. Next, lithium iron phosphate powder (interface modification material), PVDF binder, and NMP solvent are mixed and stirred to form an outermost slurry with a solid content of 55% and a viscosity adjusted to 2500 mPa·s. The core-shell intermediate is then added to the outermost slurry and ultrasonically dispersed for 45 minutes to ensure uniform slurry coating on the surface of the core-shell intermediate. A fluidized bed coating process is then used for coating, with the fluidization velocity controlled at 1.0 m / s and the coating temperature at 70°C. A second sublayer is then coated onto the surface of the first sublayer, achieving a density of 35% and a thickness of 15 nm. After sieving, complete gradient-coated lithium-replenishing particles (i.e., lithium replenishing agents) are obtained.

[0082] Step S102: Weigh lithium iron phosphate (positive electrode active material), lithium supplementer obtained in step S101, SP and PVDF in a mass ratio of 85:3:7:5, add them to NMP, and vacuum stir at 3000 rpm for 3 hours to form a positive electrode slurry with a solid content of 55%.

[0083] Step S103: The positive electrode slurry obtained in step S102 is coated on one surface of an aluminum foil (12 μm thick) along the thickness direction. The wet film thickness is 150 μm. It is then dried at 100°C for 3 hours and then pressed with an 8 MPa pressure roller to a dry film thickness of 75 μm, thus forming an active material layer with a thickness of 75 μm on the surface of the aluminum foil, and a positive electrode sheet is obtained.

[0084] Example 2

[0085] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0086] 1) Replace the interface modification material in step S101 with Li3V2(PO4)3. Accordingly, the preparation steps of the first sublayer are adjusted as follows: After vacuum drying the Li-Mg alloy particles coated with the inner layer of Li3PO4 at 110°C for 4.5h, add them to an anhydrous ethanol mixture of LiOH, V2O5, and NH4H2PO4, and add SP at the same time. After ultrasonic dispersion, stir at 90°C for 4h, and then calcine at 450°C for 2.5h in an argon atmosphere to form a first sublayer with a thickness of 200nm and a density of 60%.

[0087] 2) Replace the positive electrode active material in step S102 with Li3V2(PO4)3.

[0088] Example 3

[0089] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0090] The material of the first coating layer in step S101 is replaced with LiAlO2. Accordingly, the preparation steps of the first coating layer are adjusted as follows: gold Li-Mg alloy particles are dispersed in a 0.3 mol / L anhydrous ethanol solution containing aluminum nitrate (Al(NO3)3) and lithium hydroxide (LiOH), and the mixture is stirred at a constant temperature of 60°C for 2 hours under argon protection to form an inner layer of LiAlO2, which is the first coating layer.

[0091] Example 4

[0092] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0093] 1) In step S101, the density of the first coating layer is adjusted to 92%. Correspondingly, in the preparation step of the first coating layer, the "reacting at 40°C for 1.5h under argon protection" is adjusted to "reacting at 40°C for 1h under argon protection" to form a Li3PO4 inner layer (i.e., the first coating layer) with a thickness of 160nm and a density of 92%.

[0094] 2) In step S101, the density of the first sublayer is adjusted to 40%. Correspondingly, in the preparation step of the first sublayer, "calcined at 450°C for 2.5h in an argon atmosphere" is adjusted to "calcined at 430°C for 2.5h in an argon atmosphere" to form a first sublayer with a thickness of 200nm and a density of 40%.

[0095] Example 5

[0096] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0097] In step S101, the mass ratio of lithium iron phosphate powder to SP is adjusted to 85:5; the step of "dispersing by ultrasound and stirring at 90°C for 4 hours" in the preparation of the first sublayer is adjusted to "dispersing by ultrasound and stirring at 90°C for 3 hours". The final thickness of the first sublayer is 240 nm and the density is 60%.

[0098] Example 6

[0099] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0100] In step S101, the mass ratio of lithium iron phosphate powder to Li3PO4 is adjusted to 3:1; the step of "dispersing by ultrasound and stirring at 90°C for 4 hours" in the preparation of the first sublayer is adjusted to "dispersing by ultrasound and stirring at 90°C for 3 hours". The final thickness of the first sublayer is 230 nm and the density is 60%.

[0101] It should be noted that the mass of the inner layer of Li3PO4 can be obtained through quantitative yield calculation of the reaction, thereby enabling industrial-grade precise control of the mass ratio of lithium iron phosphate powder to Li3PO4.

[0102] Example 7

[0103] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0104] The step of forming the second sublayer is omitted in step S101, that is, the core-shell intermediate obtained is used as a lithium supplement.

[0105] Example 8

[0106] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0107] In step S101, the coating temperature of the fluidized bed coating process in the preparation of the second sublayer is adjusted from 70°C to 55°C to form a second sublayer with a thickness of 5nm and a density of 35%.

[0108] Example 9

[0109] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0110] In step S101, the coating temperature of the fluidized bed coating process in the preparation of the second sublayer is adjusted from 70°C to 80°C to form a second sublayer with a thickness of 20nm and a density of 35%.

[0111] Example 10

[0112] In this embodiment, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0113] The mass ratio of lithium iron phosphate in step S102, lithium replenishing agent obtained in step S101, SP and PVDF is adjusted to 83:5:7:5.

[0114] Comparative Example 1

[0115] In this comparative example, the preparation method of the positive electrode sheet omits step S101 compared to Example 1. Correspondingly, the step of preparing the positive electrode slurry in step S102 does not add lithium supplementation agent, and the other steps are the same as in Example 1.

[0116] Comparative Example 2

[0117] In this comparative example, the preparation method of the positive electrode sheet omits step S101 compared to Example 1. Correspondingly, in the step of preparing the positive electrode slurry in step S102, Li-Mg alloy particles, the same as those in step S101 of Example 1, are directly added as lithium supplementing agents. Other steps are the same as in Example 1.

[0118] Comparative Example 3

[0119] In this comparative example, the preparation method of the positive electrode sheet omits the step of forming the first coating layer and the second sub-layer in step S101 compared to Example 1. Instead, the first sub-layer is directly coated on the surface of the Li-Mg alloy particles to obtain the lithium replenishing agent. The other steps are the same as in Example 1.

[0120] Comparative Example 4

[0121] In this comparative example, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0122] In step S101, the density of the first coating layer is adjusted to 70%. Correspondingly, in the preparation step of the first coating layer, the "reaction at 40°C for 1.5h under argon protection" is adjusted to "reaction at 35°C for 1.2h under argon protection" to form a Li3PO4 inner layer (i.e., the first coating layer) with a thickness of 150nm and a density of 70%.

[0123] Comparative Example 5

[0124] In this comparative example, the preparation method of the positive electrode sheet omits the steps of forming the first sublayer and the second sublayer in step S101 compared to Example 1. That is, only the first coating layer is coated on the surface of the Li-Mg alloy particles to obtain the lithium replenishing agent. The other steps are the same as in Example 1.

[0125] Comparative Example 6

[0126] In this comparative example, the preparation method of the positive electrode is basically the same as that in Example 1, with the main difference being:

[0127] In step S101, the density of the first sublayer is adjusted to 90%. Accordingly, in the preparation step of the first sublayer, "calcined at 450°C for 2.5h in an argon atmosphere" is adjusted to "calcined at 450°C for 3.5h in an argon atmosphere" to form a first sublayer with a thickness of 180nm and a density of 90%.

[0128] It should be noted that the density in this application is calculated as (measured density / theoretical density) * 100%. The measured density of the first and second coating layers (including the first and second sublayers) in this application can be obtained, for example, by methods such as gas displacement or Archimedes' displacement method. When the coating material is a single component, such as the first coating layer, the theoretical density of the coating layer is the theoretical density of that single component. When the coating material is multi-component, such as the second coating layer, the theoretical density of the coating layer is calculated by weighting the theoretical densities of each component. For example, if the coating material is composed of components A and B, then the theoretical density of the coating layer = ρ A *a+ρ B *(1-a;where, ρ A Let ρ be the theoretical density of component A, a be the mass percentage of component A in the coating layer, and ρ be the density of component A. B Let be the theoretical density of component B.

[0129] The positive electrode sheets prepared in the above embodiments and comparative examples were used to prepare batteries, and the performance of the batteries was tested.

[0130] The battery preparation steps include: mixing graphite, SP, CMC, and SBR in a mass ratio of 92:2:3:3 and adding them to deionized water, stirring evenly to form a negative electrode slurry, coating the negative electrode slurry onto two surfaces along the thickness direction of the negative electrode current collector (copper foil), drying and rolling to obtain a negative electrode sheet; using a polyethylene (PE) membrane as the separator, and a 1.2 mol / L LiPF6 solution as the electrolyte, wherein the solvent is a mixed solution of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:3:4; assembling the positive electrode sheet, separator, negative electrode sheet, and electrolyte obtained in the above embodiments and comparative examples into a lithium-ion battery.

[0131] The prepared lithium-ion battery was subjected to the following tests.

[0132] (1) First Coulomb efficiency test: Under constant temperature conditions of 25℃, ① constant current charging: charge at a constant current of 0.2C until the cutoff voltage of 3.65V; ② constant voltage charging: charge at a constant voltage of 3.65V until the current drops to 0.05C, and record the total charging capacity C. 充 ③ Let stand: Let stand for 10 minutes; ④ Constant current discharge: Discharge at a constant current of 0.2C until the cutoff voltage is 2.0V, and record the total discharge capacity C.放 First Coulomb efficiency (ICE) = (C 放 / C 充 )*100%.

[0133] (2) Cyclic performance test: Under constant temperature of 25℃, the capacitor was charged to 3.65V with a constant current of 1C, then charged to 0.05C with a constant voltage, and left to stand for 5 minutes; then discharged to 2.0V with a constant current of 1C, and left to stand for 5 minutes. This is one cycle. The capacitor was continuously cycled 500 times, and the discharge capacity of each cycle was recorded. The capacity retention rate after 500 cycles = (C500 / C1)*100%; where C1 is the discharge capacity of the first cycle and C500 is the discharge capacity of the 500th cycle.

[0134] (3) Room temperature interface impedance test: Under the condition of 25℃±2℃, ① Battery pretreatment: Charge the battery after 500 cycles to 3.2V (lithium iron phosphate platform voltage), let it stand for 30 minutes to ensure that the battery is in a stable state; ② AC impedance test: Use an electrochemical workstation to apply an AC disturbance signal with an amplitude of 5mV, and test the frequency range of 100kHz~0.01Hz; ③ Data extraction: Fit the Nyquist plot obtained from the test, and extract the intersection value of the high frequency region and the real axis, which is the room temperature interface impedance of the battery.

[0135] The test results are shown in Table 1.

[0136] Table 1

[0137]

[0138] As can be seen from the data in Table 1, Comparative Example 2, compared to Comparative Example 1, added Li-Mg alloy particles as a lithium replenisher to the positive electrode. However, since the Li-Mg alloy particles lack a coating layer, they cannot effectively replenish lithium. Therefore, the electrochemical performance of the battery in Comparative Example 2 is basically not improved compared to Comparative Example 1. The lithium replenishers prepared in Comparative Examples 3 and 5 only have a second or first coating layer on the surface of the Li-Mg alloy particles, which is insufficient to guarantee the effectiveness of the lithium replenisher, and the electrochemical performance of the corresponding batteries cannot be effectively improved. In Comparative Example 4, the density of the first coating layer is too low. On the one hand, the first coating layer cannot perform its core functions of insulation and controlled lithium release, resulting in uncontrolled lithium release rate, a significant decrease in lithium source utilization, and difficulty in effectively compensating for irreversible lithium loss, thus limiting the improvement of the initial coulombic efficiency. On the other hand, the electrolyte easily permeates through the pores to the core surface, causing lithium oxidation corrosion, side reaction gas production, and lithium dendrite growth, which seriously affects the safety and cycle stability of the battery. In Comparative Example 6, the excessive density of the first sublayer hindered ion / electron transport and failed to adequately buffer the volume expansion of the core, leading to deteriorated interfacial compatibility and consequently, a lack of effective improvement in the battery's electrochemical performance. The batteries containing the positive electrode sheets prepared in Examples 1 to 10 exhibited significantly improved initial coulombic efficiency and 500-cycle capacity retention compared to the battery containing the positive electrode sheet prepared in Comparative Example 1, while also showing a significant reduction in room-temperature interfacial impedance. Therefore, in this application, the synergistic effect of a first coating layer with a density greater than or equal to 92% and a second coating layer with a density less than or equal to 80% not only ensures the stability of the lithium replenishment core but also guarantees the controllable release and rapid transport of lithium ions, optimizes interfacial contact, improves the lithium source utilization of the lithium replenishment, matches the overall electrochemical characteristics of the electrode, and reduces interfacial impedance, thereby ensuring battery safety and improving initial coulombic efficiency and cycle performance.

[0139] This application provides a battery cathode based on a gradient-coated lithium replenishing agent. The lithium replenishing agent, through a "core-double-shell" gradient coating structure, solves the problems of low initial coulombic efficiency, rapid cycle capacity decay, and high interfacial impedance of traditional battery electrodes (such as lithium iron phosphate battery electrodes). By gradient coating the lithium replenishing material (core), the stable presence of the lithium replenishing agent, the controllable release of active lithium, and the efficient interfacial bonding with the positive electrode active material are achieved, effectively improving the overall performance of the battery.

[0140] It should be noted that the positive electrode sheet embodiments and battery embodiments provided in this application belong to the same concept; the technical features in the technical solutions described in each embodiment can be arbitrarily combined without conflict.

[0141] It should be understood that the above embodiments are exemplary and not intended to encompass all possible implementations. Various modifications and changes can be made to the above embodiments without departing from the scope of this disclosure. Similarly, the various technical features of the above embodiments can be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only illustrate several implementations of the present invention and do not limit the scope of protection of this patent.

Claims

1. A positive electrode plate, characterized in that, It includes a current collector and an active material layer disposed on at least one side surface of the current collector along the thickness direction; the active material layer includes a positive electrode active material and a lithium supplement agent; The lithium replenishing agent has a core-shell structure, including a core and a first coating layer and a second coating layer that sequentially cover the core from the inside out; the core includes metallic lithium and / or lithium alloy, the material of the first coating layer is an ion-conducting but non-conducting electronic material, the second coating layer includes an interface modification material, the interface modification material being the same as the positive electrode active material; the density of the first coating layer is greater than or equal to 92%, and the density of the second coating layer is less than or equal to 80%.

2. The positive electrode sheet according to claim 1, characterized in that, The kernel has a particle size of 1μm to 5μm.

3. The positive electrode sheet according to claim 1, characterized in that, The material of the first coating layer includes at least one of Li3PO4, LiAlO2, Al2O3, ZrO2, and Li3N, preferably Li3PO4; and / or, The interface modification material includes at least one of lithium iron phosphate, lithium vanadium phosphate, ternary cathode material, lithium manganese oxide, and lithium cobalt oxide, preferably lithium iron phosphate.

4. The positive electrode sheet according to claim 1, characterized in that, The second coating layer further includes a conductive agent; optionally, the mass ratio of the interface modification material to the conductive agent is (85~95):(5~15).

5. The positive electrode sheet according to claim 1, characterized in that, The mass ratio of the first coating layer to the second coating layer is (20~40):(60~80).

6. The positive electrode sheet according to claim 1, characterized in that, The thickness of the first coating layer is 80nm~250nm; and / or, The thickness of the second coating layer is 100nm~320nm.

7. The positive electrode sheet according to any one of claims 1-6, characterized in that, The second coating layer includes a first sublayer and a second sublayer, wherein the first sublayer is located between the first coating layer and the second sublayer, and the density of the first sublayer is greater than that of the second sublayer.

8. The positive electrode sheet according to claim 7, characterized in that, The compactness of the first sublayer is greater than or equal to 40%; and / or, The density of the second sublayer is 25%~35%; and / or, The thickness of the first sublayer is 100nm~300nm; and / or, The thickness of the second sublayer is 5nm~20nm, preferably 10nm~15nm.

9. The positive electrode sheet according to claim 1, characterized in that, The mass ratio of the lithium supplement to the positive electrode active material is (1~5):100; and / or, The particle size ratio of the lithium supplement to the positive electrode active material is 1:(5~10).

10. A battery, characterized in that, Includes the positive electrode sheet as described in any one of claims 1-9.